Research in solutions of reducing pour-point on crude oil production and transportation - Dương , Chí Trung; Lưu , Hoài Phương; Hoàng, Thịnh Nhân (Journal of Technical Education Science, 2013)
Research focuses on solutions of reducing pour point of high viscous crude oil from oil fields of Vietnam (Bach Ho), Russia (Stavrapol, Kolvin) and Ucraina (Ucraina). The main target of the experiments is to optimize receipt of crude oils mixture and inbihitor concentration; and to analysis pour point characteristics of crude oil by using ultrasound and combination with inhibitor DMN-2005. The results showed that mixture method combining with using inhibitor allow reducing significantly amount of inhibitor and increasing ratio of high viscous oil in the same pour point reducing request. The experiments also pointed out that combination of using inhibitor and ultrasound reduced considerably pour point of crude oil and improved dramatically its rheological characteristics, especially on high resin content crude oil.